2005
DOI: 10.1073/pnas.0500597102
|View full text |Cite
|
Sign up to set email alerts
|

A specific subdomain in φ29 DNA polymerase confers both processivity and strand-displacement capacity

Abstract: Recent crystallographic studies of 29 DNA polymerase have provided structural insights into its strand displacement and processivity. A specific insertion named terminal protein region 2 (TPR2), present only in protein-primed DNA polymerases, together with the exonuclease, thumb, and palm subdomains, forms two tori capable of interacting with DNA. To analyze the functional role of this insertion, we constructed a 29 DNA polymerase deletion mutant lacking TPR2 amino acid residues Asp-398 to Glu-420. Biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 37 publications
4
102
0
Order By: Relevance
“…As mentioned in the introductory section, protein-primed DNA polymerases contain two insertions, TPR1 and TPR2, which in the case of Φ29DNAP are involved in interactions with the TP and in processivity and strand displacement, respectively (22,23). Recent work has suggested that TPR2 also may be required for TLS capacity in a transposon-derived protein-primed DNA polymerase (54).…”
Section: B35dnap Tls Is Counteracted By Proofreading Activity Up To 5 Ntmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introductory section, protein-primed DNA polymerases contain two insertions, TPR1 and TPR2, which in the case of Φ29DNAP are involved in interactions with the TP and in processivity and strand displacement, respectively (22,23). Recent work has suggested that TPR2 also may be required for TLS capacity in a transposon-derived protein-primed DNA polymerase (54).…”
Section: B35dnap Tls Is Counteracted By Proofreading Activity Up To 5 Ntmentioning
confidence: 99%
“…This designation refers to their capacity, apparent for adenoviruses as well as different bacteriophage enzymes (20,21), to perform genome replication primed by a specific protein, termed terminal protein (TP), that becomes covalently linked to the 5′ DNA ends. Identification and annotation of these polymerases in databases is based on the presence of two specific amino acid insertions, TPR1 and TPR2, involved in the interaction with TP and in processivity and strand displacement capacity, respectively (22,23).…”
mentioning
confidence: 99%
“…By analogy to a right hand, polymerase domains are conventionally divided into palm, finger, and thumb subdomains, which are involved in binding the catalytic metal ions, the incoming dNTP, and the duplex product DNA, respectively (Steitz et al, 1994). The two subdomains that are unique to protein-primed polymerases, TPR1 and TPR2, are insertions in the palm subdomain involved in interaction with terminal protein (Dufour et al, 2000(Dufour et al, , 2003, and in processivity and strand displacement (Kamtekar et al, 2004;Rodríguez et al, 2005).…”
Section: Structure Determinationmentioning
confidence: 99%
“…We made a deletion in the TPR2 subdomain and found that the resulting DNA polymerase had a reduced DNA binding and had lost its processivity and stranddisplacement capacity. 18 The crystal structure of the ø29 DNA polymerase/TP heterodimer was also obtained in collaboration with Tom Steitz's laboratory 11 showing three domains in the TP: the N-terminal domain that has sequence-independent DNA binding capacity and does not interact with the DNA polymerase; the intermediate domain that interacts with the TPR1 subdomain of the polymerase; and the priming domain, which contains Ser232 and occupies the same binding cleft in the polymerase as duplex DNA does during elongation. The N-terminal domain is responsible for the nucleoid association of the TP.…”
Section: Postdoctoral Trainingmentioning
confidence: 99%